2018
DOI: 10.1177/1526602818756610
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Angiographic Dissection Patterns Caused by Long vs Short Balloons During Balloon Angioplasty of Chronic Femoropopliteal Occlusions

Abstract: Using long balloons for balloon angioplasty may help prevent severe vessel dissection in chronic femoropopliteal occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…When the lesion was longer, the scoring balloon was dilated in the lesion first for a few seconds and then balloons longer than the lesion length were used for long inflation thereafter. 18 When the first scoring or conventional balloon dilation was considered to be too small based on angiography and IVUS findings, another balloon with a larger diameter was employed. Balloons were usually inflated at nominal pressure, which was raised to rated-burst pressure if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…When the lesion was longer, the scoring balloon was dilated in the lesion first for a few seconds and then balloons longer than the lesion length were used for long inflation thereafter. 18 When the first scoring or conventional balloon dilation was considered to be too small based on angiography and IVUS findings, another balloon with a larger diameter was employed. Balloons were usually inflated at nominal pressure, which was raised to rated-burst pressure if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has been demonstrated that the length of the balloon may play a significant role for the occurrence of dissections after BA. Tan et al 86 compared the incidence and severity of post-BA dissections after the use of longer and shorter balloons and suggested that the risk of balloon edge dissections was lower for lesions treated with balloons ≥200 mm vs balloons ≤150 mm. Thus, post-BA dissection could be prevented by the use of longer balloons, which reduce the number of required dilations over long infrapopliteal lesions.…”
Section: Postdilation Dissectionmentioning
confidence: 99%
“…Previous reports demonstrated that balloon dilation for 3 minutes was more effective in preventing severe postdilation dissection compared with 1 minute. 11,12 However, there are no studies that have investigated whether inflation time longer than 3 minutes is beneficial in reducing postprocedural dissection.…”
Section: Introductionmentioning
confidence: 99%